Stagnation Point Solution Due to a Continuously Stretching Surface with Applied Magnetic Field Using HAM - Seshadri, Rajeswari; Munjam, Shankar Rao (Journal of Applied Nonlinear Dynamics, 2026)
In the present study, we consider the steady two-dimensional stagnation point flow due to a stretching surface in an ambient fluid. The fluid is viscous, incompressible and electrically conducting near the stagnation region on a stretching surface. A uniform magnetic field of strength B is applied in the positive y.direction normal to the stretching surface. The equations governing the flow are solved using Homotopy Analysis Method (HAM). The flow variables are computed in the form of a series with its coefficients containing the parameters such as the magnetic field and the ratio of stretching velocity so that the effect of these parameters on the flow variables can be computed without much computational effort. The optimal values of the convergence control parameters and the the averaged squared residual errors are computed for the flow variables. The software Mathematica is used to perform all the semi-analytical calculations. It was observed that the effect of ratio of stretching velocity V0 on flow velocity is very significant in the sense that zero skin friction occurs at V0 = 0.5. and the trend in the variation of velocity profiles as well as skin friction coefficients are just opposite for V0 < 0.5 and V0 > 0.5.